Innovative ultrasound imaging techniques : biomedical applications - Bridal, S. Lori; Ohio Library and Information Network (London, UK : ISTE Ltd ; Hoboken NJ : John Wiley & Sons, Inc., 2024)
This book provides an understanding of ultrasound imaging principles and how the field is evolving to better probe living systems. Today, widely-used imaging systems visualize structures and blood flow within the body in real-time. Signal analysis, hardware and contrast agent innovations are extending the capacity of ultrasound to assess tissue elasticity, to enable three-dimensional viewing of moving structures and to detect vessels smaller than the wavelength-limited resolution. Techniques are also being designed so that we are less impeded by bones in the sound path, as well as to combine light and sound to detect optically-absorbent structures within the body. After an introductory chapter reviewing the key basic concepts, each chapter presents a detailed explanation focusing on a specific set of key principles and then shows the related techniques in each domain that are currently being refined to evaluate living systems in greater depth
Keywords: Diagnostic ultrasonic imaging; Ultrasonography